PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS MULTIPLE INTELEGENCES (MI) UNTUK MELATIH KETERAMPILAN BERPIKIR KRITIS PESERTA DIDIK PADA MATERI INTERAKSI MAKHLUK HIDUP DENGAN LINGKUNGANNYA KELAS VII SMP - Melani Chrisdayanthi Sijabat; Mariani Natalina L; Suwondo Suwondo (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to produce student worksheets based Multiple Intelegences (MI) to train critical thinking skills on quality material for the interaction of living things with their environment in class VII junior high school. This research was carried out at the Biology Educations Laboratory of Teacher Training and Educations, University of Riau and the state junior high school 1 Pekanbaru in October 2020- January 2021. The type of research used is Research and Development (R&D) with the ADDIE’S research model consisting of 5 stages, namely analysis, design, development, implementation and evaluation. In this research, it is limited only to the development stage. Data collection instruments in the form of validation sheets and questionnaires of respondens. The results of the validation of student worksheets based Multiple Intelegences (MI) to train critical thinking skills are at an average value of 3.68 with a very valid category. The results of the limited test score are 3.64 with a very good category. Thus, student worksheets based Multiple Intelegences (MI) to train critical thinking skills in the material on the interaction of living things with their environment class VII junior high school has been successfully developed with a very good quality and can be implemented on a wider scale.Key Words: Student Worksheets, Multiple Intelegences, Critical Thinking Skills